Evolução da produção ambulatorial dos Centros de Especialidades Odontológicas do Brasil no período de 2010 a 2016 - Silva, Amanda Lúcio Do Ó (2019)
Introduction: The National Program for Improving Access and Quality of Dental Specialties Centers was launched in 2013 providing financial incentive for the CEOs who performed the adhesion and complied with agreed quality standards. Objective: To analyze the impact of PMAQ-CEO on Brazilian CEO productions. Methodology: The universe was composed of all CEOs in Brazil who participated in the External Evaluation (n=980). Excluded from the sample were CEOs who had no production registered for two consecutive years. Perforating the sample only the CEOs who held production record in all specialties in the period (n=764). The production data of the CEOs from 2010 to 2016 were collected from the specialties: Periodontics, Endodontics and Surgery. Available in the Outpatient Information System (SIA - DataSUS). The data was tabulated and analyzed in IBM SPSS Statistics 22 and Excel, version 2000 (Microsoft Corp.). The descriptive data were analyzed by year, Type of CEO and geographic region. The absolute numbers were separated into before and after PMAQ-CEO. The Wilcoxon median difference test was performed. Results: The production of CEOs in t1 was 8,640,895 and t2 with 10,568,933, with an increase of 22.3%, (1,928,038 procedures). There was an increase in production in Surgery (105.93%) and Periodontics (11.3%) and in Endodontics reduction of 28.3%. Among the regions, the Northeast presented a 50.8% increase, followed by the South (13.8%) and a decrease in the Southeast (18.3%). CEO Type II represented the highest percentage increase (36.2%), Type I and III CEOs fell 10.6% and 31.0%, respectively. The Wilcoxon test revealed statistical significance for the increase of national production in the South region, in Type II CEOs and in the Surgery specialty. Conclusion: PMAQ-CEO positively impacted CEO output, with emphasis on the Northeast Region, Type II CEOs and the Surgery specialty.